The mediating role of internal marketing on the drivers of the service excellence performance - Hasfizani, Ariffin (2021)
Assessing the performance of the service is challenging, since the character of the service is unique, making it difficult to produce and measure, but the importance of service development in any sector is critical. Hence, this study assesses aspects related to conceptualisations and measurement models on service excellence performance in higher education perspectives. In providing the world's leading high-quality educational hub, the Malaysian higher education sector must balance academic and non-academic performance. This thesis therefore analysed the drivers of the performance of service excellence to be implemented at Malaysian public universities within non-academic units/departments. The goal of this study is to fill the knowledge gaps in the implementation of the service excellence performance at Malaysian Public Universities. This research therefore proposed and analysed the service excellence performance model underpinned by the Resources Advantage (R-A) Theory. This study proposed Managerial Competency, Productive Service Employee and Technology Innovation as the Service Excellence Drivers with Internal Marketing served as the intervening variable towards Service Excellence Performance as the dependent variable. The study involved two groups of respondents with a total of 490 administrators /managers and internal clients at the non-academic units/departments of nineteen Malaysian public universities. This study employed quantitative approach with closed-ended questionnaires. The results indicated that the productive service employee contributed greatly to the performance of service excellence in the nonacademic departments in the Malaysian public universities. The results of the study contributed theoretically, methodologically and practically to the implementation of the service excellence performance to literature, practitioners at Malaysian public universities, the Malaysian higher education industry and future researchers in a related field of study.